Histological Findings Of Helicobacter Pylori In Diabetic Patients - Rehmat Ullah, Kapeel Raja, Yasir Abbas Zaidi, Asma Abdul Razzak, Usamah Saeed Butt, Kainat Kanwal, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The aim of this study was to determine the histological findings of H-pylori in diabetic patients. Material and methods: This observation study was conducted on 90 diabetic patients with H-pylori infection at Gastroenterology Department, Nishtar Medical University, Multan in the duration from November, 2022 to April, 2023. Endoscopic and histological findings were determined. Chi Square test was applied with P value less than 0.05. Results: The mean age was 53.73±8.66 years with majority male patients. On histological findings chronic gastritis was seen in 74.4%, gastric atrophy 18.9% and intestinal metaplasia 6.7%. Conclusion: The histological findings of H-pylori in diabetic patients were chronic gastritis 74.4%, gastric atrophy 18.9% and intestinal metaplasia 6.7%. Keywords: H-pylori, Diabetes, Histological findings, Endoscopy